Pinocchio - Collodi, Carlo; Gioia Fiammenghi (Illustrator); E. Harden (Translator) (London, Puffin, 2011)
Pinocchio, a wooden puppet full of tricks and mischief, with a talent for getting into and out of trouble, wants more than anything else to become a real boy, but first he must learn to be truly unselfish.